South of Broad : a novel - Conroy, Pat (Nan A. Talese : Doubleday, 2009)
Leopold Bloom King, our narrator, is the son of an amiable, loving father who teaches science at the local high school. His mother, an ex-nun, is the high school principal and a well-known Joyce scholar. After Leo's older brother commits suicide at the age of thirteen, the family struggles with the shattering effects of his death. Eventually he becomes part of a tightly knit group of high school seniors that includes friends Sheba and Trevor Poe, glamorous twins with an alcoholic mother and a prison-escapee father; hardscrabble mountain runaways Niles and Starla Whitehead; socialite Molly Huger and her boyfriend, Chadworth Rutledge X; and an ever-widening circle whose liaisons will ripple across two decades-from 1960s counterculture through the dawn of the AIDS crisis in the 1980s.